The muon g − 2 anomaly confronts new physics in e ± and μ ± final states scattering - Luc Darmé; Giovanni Grilli di Cortona; Enrico Nardi (Journal of High Energy Physics, 2022)
Abstract The 4.2σ discrepancy between the standard model prediction for the muon anomalous magnetic moment a μ and the experimental result is accompanied by other anomalies. A crucial input for the prediction is the hadronic vacuum polarization a μ HVP $$ {a}_{μ}^{HVP} $$ inferred from σ had = σ(e + e − → hadrons) data. However, the two most accurate determinations of σ had from KLOE and BaBar disagree by almost 3 σ. Additionally, the combined data-driven result disagrees with the most precise lattice determination of a μ HVP $$ {a}_{μ}^{HVP} $$ by 2.1 σ. We show that all these discrepancies could be accounted for by a new boson produced resonantly around the KLOE centre of mass energy and decaying promptly yielding e + e − and μ + μ − pairs in the final states. This gives rise to three different effects: (i) the additional e + e − events will affect the KLOE luminosity determination based on measurements of the Bhabha cross section, and in turn the inferred value of σ had; (ii) the additional μ + μ − events will affect the determination of σ had via the (luminosity independent) measurement of the ratio of π + π − γ versus μ + μ − γ events; (iii) loops involving the new boson would contribute directly to the prediction for a μ . We discuss in detail this possibility, and we present a simple model that can reconcile the KLOE and BaBar results for σ had, the data-driven and the lattice determinations of a μ HVP $$ {a}_{μ}^{HVP} $$ , the predicted and measured values of a μ , while complying with all phenomenological constraints.